A detailed smoking history and determination of MYC status predict response to checkpoint inhibitors in advanced non-small cell lung cancer - Chiu, Michelle (Transl Lung Cancer Res, 2020)
BACKGROUND: Although many studies have determined that PD-L1 expression by immunohistochemistry can be somewhat predictive of a response to checkpoint inhibitor the impact of specific genomic changes and smoking history in the context of PD-L1 expression is limited. This single-center study examined clinical and genomic factors beyond STK11 and EGFR in patients with advanced non-small cell lung cancer (NSCLC) to determine which patients benefit from therapy with immune checkpoint inhibitors (ICIs). METHODS: Clinical and genomic features of patients with NSCLC treated with immunotherapy were compiled into a database. Genomic information collected included gene mutations via next generation sequencing, tumor mutation burden (TMB), and PD-L1 tumor proportional scores. RESULTS: A total of 131 patients with advanced NSCLC treated with ICIs were examined. Race was not associated with response. A positive response to immunotherapy was associated with smoke year increase (P=0.042). KRAS mutation and MYC amplification were associated with a positive response to immunotherapy while EGFR, RB1, and NF1 mutations were associated with a lack of response. KRAS mutation (P=0.007) and high TMB (P=0.070) were positively associated with smoking history. EGFR mutation was negatively associated with smoking history (P=0.002) . In multivariate analysis controlling for age and smoking history, MYC amplification continued to be the only predictive genomic marker with a trend toward response to therapy (P=0.092) beyond the smoking history. CONCLUSIONS: Among the clinical and genomic factors examined in this study, smoking status is the most predictive of response to ICIs. Only MYC amplification continued to predict a trend toward response to immunotherapy when controlling for smoking history. Other genomic predictors such as EGFR and KRAS simply reflect their association with smoking. Detailed smoking history and MYC amplification alone can predict response to ICI.